The Effect of Electronic Record Keeping and Transesophageal Echocardiography on Task Distribution, Workload, and Vigilance During Cardiac Anesthesia - Weinger, Matthew B.; Herndon, Oliver W.; Gaba, David M. (Anesthesiology (Philadelphia), 1997)
Electronic anesthesia record keeping (EARK) systems increasingly are used in the operating room, but studies have only recently begun to investigate their effect on anesthesia task performance. Teak analysis, workload assessment, and vigilance assessment techniques were used to study senior residents providing anesthesia for coronary artery bypass graft (CABG) procedures. The impact on anesthesia residents' workload of the routine use of transesophageal echocardiography (TEE) also was examined. Before each case, the record keeping system was randomly selected as either electronic (Distek ARKIVE; EARK) or traditional manual recording (MAN). Twenty CABG procedures (10 EARK and 10 MAN) were examined, with observation commencing with anesthetic induction and terminating on initiation of cardiopulmonary bypass. The activities of each resident, divided into 32 task categories (e.g., "laryngoscopy," "observe monitors," etc.), were recorded by a trained observer using a computer. The response latency to a randomly activated alarm light was used as a measure of vigilance ("vigilance latency"). Workload was rated by subject and observer at random 10- to 15-min intervals throughout the case. Data analysis included calculation of workload density (number of tasks/min multiplied by task-specific workload values) and task-links (relationship between sequential tasks). The two groups had a similar distribution of tasks before intubation. In only 4 of the 20 cases studied did any manual record keeping occur before intubation. After intubation, the EARK group spent less time record keeping and using the TEE but more time observing the monitors and conversing with the attending physician than the MAN group did. All subjects reported significantly higher workload scores before intubation compared with after intubation. Similarly, vigilance latency was greater before intubation compared with after intubation (57 vs. 31 s; P < 0.001). There were no significant differences between the two record keeping groups in subjective workload scores, workload density, or vigilance latency. During TEE use, vigilance latency was significantly longer, and workload density was greater than during other monitoring or recording tasks. This study provides an objective description of the task distribution and workload during the administration of anesthesia for cardiac surgery. Under the conditions of this study. EARK use modestly decreased the time spent record keeping during the postintubation prebypass period. However, there was no effect of EARK either on vigilance or several measures of workload. TEE use was associated with increased workload and possibly decreased vigilance.